PERBANDINGAN HASIL BELAJAR FISIKA SISWA MATERI POKOK GELOMBANG DENGAN MENGGUNAKAN METODE RESTASI DAN METODE DISKUSI DI KELAS VIII SMP NEGERI 3 PADANGSIDIMPUAN - Sari Wahyuni Rozi Nasution (JURNAL PhysEdu (PHYSICS EDUCATION), 2024)
This study aims to look at the picture of the results of learning subject matter wave physics using a method in a class recitation SMP Negeri 3 Padangsidimpuan , to describe the learning outcomes of the subject matter wave physics using a method in a class discussion SMP Negeri 3 Padangsidimpuan , and to see whether there differences in learning outcomes physics subject matter waves using the method of recitation and discussion in class VIII SMP Negeri 3 Padangsidimpuan . This research was carried out by using the experimental method to see the difference of implementation measures . The population in this study were all students of Class VIII SMP Negeri 3 Padangsidimpuan which consists of 8 classes totaling 304 people . The sampling technique used was cluster random sampling technique , so that the sample obtained in class VIII1 = 38 and = 38 VIII2 class numbered 76 people . The data collected was analyzed in two ways : first descriptive analysis to see the general description of the two variables , and then to determine whether there is a difference between the two variables we used t - tests to test Sudjana . Meanwhile, to capture the necessary data is done with the test . In order to obtain data on the outcomes of learning subject matter wave physics using recitation methods and discussion methods. Learning outcomes of the research subject matter wave physics using the recitation obtained an average of 76.33 in the category of " Good " . If consultation with the criteria in Table 4 Chapter III . While the value of the subject matter wave physics learning using discussion method obtained an average of 72.89 in the category of " Good " . If consulted in Table 4 Chapter III . Based on calculations performed obtained values ​​" of t " at 2.11 , while the 5 % significance level and df = n1 + n2 - 2 = 38 + 38-2 = 74 . Ttable value at 5 % significance level of 74 is 1.66 . Based on the calculation above it can be concluded that of t greater than ttable ( tcount > ttable = 2.11 > 1.66 ) . Means hypothesis upheld in this study can be accepted or approved . That is There a Difference Physics Learning Outcomes Topic Wave Method using recitation and Methods Discussion in class VIII SMP Negeri 3 Padangsidimpuan.